An Optimal Blade Design for Mini Wind Generators Mountable on the Spoiler of a Vehicle - del Riego, Daniel Gonzalez (2022)
In this work, a mini wind turbine was developed that takes advantage of the kinetic energy of the winds around a moving car. The blades were designed according to inclination angles in order to capture as much energy as possible without greatly affecting the performance of the vehicle. Various proposals are presented according to the inclination of the angle of the blades with respect to the axis of the turbine. Likewise, the behavior of airflow over the blades will be studied using CFD techniques. In addition, it will be possible to obtain various parameters such as the drag coefficient that will serve for the optimal design of the turbines. Finally, experimentation will be carried out to evaluate the electrical energy that said turbine can produce when coupled to a mini generator. The results show that the most optimal design is proposal 2 because it is the one that produces more voltage with less drag force.